PENGARUH KONSENTRASI TEPUNG ASTAXANTHIN PADA PAKAN TERHADAP PENINGKATAN WARNA IKAN MASKOKI (Carassius auratus) Effect of Astaxanthin Concentration in Diet to Increase Color Of Goldfish (Carassius auratus) - Artha Maria Gabriella Sitorus; Syammaun Usman; Nurmatias Nurmatias (AQUACOASTMARINE, 2015)
Goldfish in Indonesia is popular and likely ornamental fish for all of society. Goldfish have a stable price in the market and quite affordable with the ever-increasing market demand. Goldfish as ornamental fish have interesting colour and excellence in body shapes especially the beauty of their fins. The bright and brilliant colors of Goldfish is an attraction that affect it economical values. Thus, the color should be upgraded and maintained its quality. Such efforts to increase color will be done by pigments manipulation techniques with adding suplement into the feeds. The suplement pigments can be obtained from Astaxanthin. The purpose of this research is to know dosage Astaxanthin that optimal to increase the color of Goldfish.this research using Complete Random Design (CRD) with three repetition, with the dose treatment by 0%, 1%, 3%, and 5% for up during 28 days. Additional Astaxanthin through the feed can increasing colors of the Goldfish. The nutrient that enriched with Astaxanthin dosage is 1% can produce brighter colors than the other dose. Additional Astaxanthin in the feed has no effect on growth of GoldfishKeywords : Astaxanthin, Carassius auratus, Color, Goldfish